CHRONIC PRURITUS - Susana Brás; Cristina Amaro; Jorge Cardoso (Journal of the Portuguese Society of Dermatology and Venereology, 2015)
Chronic pruritus is a symptom that has a significant impact on the patient’s quality of life. It can be associated with a wide broad of diseases and in most of the times is difficult to treat. The search for the underlying etiology of pruritus usually requires a meticulous history taking as well as a clinical examination and laboratory investigations. Management of pruritus is often a challenge for the dermatologist and can be achieved by implementing several therapeutic approaches. This review highlights the clinical approach and the treatment of chronic pruritus.